2021
DOI: 10.1016/j.bbih.2021.100243
|View full text |Cite
|
Sign up to set email alerts
|

Outside-in induction of the IFITM3 trafficking system by infections, including SARS-CoV-2, in the pathobiology of Alzheimer’s disease

Abstract: Background IFITM3 is a viral restriction protein that enables sequestration of viral particles and subsequent trafficking to lysosomes. Recently, IFITM3 upregulation was found to induce gamma – secretase activity and the production of amyloid beta. The purpose of this study was to determine whether dysregulation of IFITM3-dependent pathways was present in neurons and peripheral immune cells donated by AD patients. As a secondary aim, we sought to determine whether these perturbations could be indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…Our results further show that Ifitm3 – one of the genes stimulated by type I interferons, as well as by proinflammatory cytokines that are critical mediators of the host innate immune response, including IL-1b, IL-6, and TNF [ 35 ] – is positively regulated by BIN1, both in vitro and in vivo. A recent publication found IFITM3 gene networks to be enriched in tau tangle-containing neurons and peripheral mononuclear cells from AD patients [ 38 ]. Expression of IFITM3 is also upregulated in microglia of a transgenic model of AD amyloid pathogenesis [ 33 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results further show that Ifitm3 – one of the genes stimulated by type I interferons, as well as by proinflammatory cytokines that are critical mediators of the host innate immune response, including IL-1b, IL-6, and TNF [ 35 ] – is positively regulated by BIN1, both in vitro and in vivo. A recent publication found IFITM3 gene networks to be enriched in tau tangle-containing neurons and peripheral mononuclear cells from AD patients [ 38 ]. Expression of IFITM3 is also upregulated in microglia of a transgenic model of AD amyloid pathogenesis [ 33 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…IFITM3 facilitates lysosome acidification [ 34 , 35 ] and limits immune-response cytokine production [ 36 , 37 ]. Notably, IFITM3 gene networks are enriched in brains and peripheral blood mononuclear cells of AD patients [ 38 ], suggesting that IFITM3 plays a role in microglial inflammatory responses to AD pathology. Collectively, these findings provide important insights into BIN1 expression and function in microglia, demonstrating the significance of microglial BIN1 expression in brain inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…In recently published work by Vavougios and colleagues ( 46 ), disrupted proteostasis and trained immunity pathways were among overlapping molecular pathways that are common across different tissues in AD. This work suggested that IFN-1 has a specific relationship with unique signaling cascades, focusing on the IFN response to antiviral effectors, such as the interferon-inducible transmembrane (IFITM) and the 2′-5′-oligoadenylate synthase (OAS) family genes in both AD and COVID-19 ( 15 ). The specific relationship of perturbed IFN-I signaling to both AD and COVID-19, focuses on interferon responsive antiviral effectors, such as IFITMs and OASs, which are interferon stimulated (ISGs) gene families that provide cellular-level defense against intracellular pathogens.…”
Section: The Viral Lifecycle: Kinase Recruitment and Tauopathymentioning
confidence: 99%
“…Dysfunctions of IFITMs and OASs on a pathway level not only have the potential to abrogate antiviral activity, but several studies suggest this dysfunction enables these factors to act as pro-viral factors ( 47 49 ). Vavougios and colleagues found that IFN-I signatures containing members of these ISG families are common in neurons, peripheral immune cells, and microglia affected by COVID-19 or by AD ( 10 , 15 , 33 , 50 , 51 ).…”
Section: The Viral Lifecycle: Kinase Recruitment and Tauopathymentioning
confidence: 99%
See 1 more Smart Citation